IMMOBILISASI SUSPENSI AKTIF PADA PELLET AMMONIA OXIDIZERS UNTUK PENGOLAHAN LIMBAH URIN KAMBING MENJADI PUPUK N - Atita Arli Tiara; I Wayan Budiarsa Suyasa; I Gusti Ayu Kunti Sri Panca Dewi (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2019)
Livestock waste that is thrown away without being processed will cause environmental pollution, therefore an effort is needed to process the livestock waste is to be processed into organic fertilizer. The part of livestock waste that can be used as organic fertilizer is urine, in this study goat urine is used. This study aims to find the best nutrients for seeding active suspension, look for the optimal dosage and time for processing goat urine into N fertilizer. The method used in this study is to immobilized the active suspension into the ammonia oxidizers pellets for later used in the goat urine treatment process with an aeration system, so that a nitrification reaction occurs which results is decrease ammonia and nitrite levels and increase nitrate levels. The results obtained in this study are the nutrients that are best used for seeding active suspension are media II that is 5 grams NPK fertilizer; 2,5 grams NH4Cl; and 5 grams glucose with MLVSS values ??of 9000 mg/L at 18 hours. The processing of goat urine obtained optimal results at pellet dosage of 20% (w/v) with optimal time at 18th hour. Ammonia level obtained was 5.6811 mg/L, nitrite levels of 2.3992 mg/L, and nitrate levels of 10.6618 mg/L. Keywords: Immobilization; active suspension; MLVSS; pellets; ammonia oxidizers; nitrification